On-line efficiency optimization control of a slip angular frequency controlled induction motor drive using neural networks - Choi, Ick; Kwon, Soon H.; Choi, J.Y.; Kim, J.W.; Kim, K.B. (IECON Proceedings (Industrial Electronics Conference), 1996)
On-line efficiency optimization control of an induction motor drive is important from the viewpoints of energy saving and controlling a system whose characteristics are not fully unknown. The paper presents a neural network-based on-line efficiency optimization control for an induction motor drive which adopts a slip angular frequency control. In the proposed scheme, a neuro-controller adjusts the slip angular frequency adaptively for minimum loss operation based on the measured input power. Simulation results show that a considerable energy saving is achieved in comparison with the conventional method of operating under the condition of constant voltage to frequency ratio (v/f).